Performance Evaluation of Green Cushion Gum Composite Formulated Based on Hybrid Filler and Curing System - Santi Puspitasari; Adi Cifriadi; Arief Ramadhan; Mochamad Chalid (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
Cushion gum is a type of rubber composite material used as adhesive in the manufacture of retread tires. Therefore, cushion gum should have good processability and mechanical characteristics, particularly tensile property, and adhesion strength. The effect of hybrid filler and curing system on the performance of green cushion gum composite was investigated to determine the appropriate green cushion gum formula designed at a laboratory scale. The content of CB N330/lignin in hybrid filler was arranged at 40/10 phr and 50/10 phr. Meanwhile, the curing system was performed semi-efficient (CBS/S 1.6/1.6 phr) and conventional (CBS/S 1.6/2.2 phr). Green cushion gum composite was also formulated using pine tar oil as a bio plasticizer. Referred to the curing characteristic and mechanical property test result, it showed that green cushion gum composite formula coded by RF1 which composed of CB N330/lignin as 50/10 phr and applied conventional curing system which ratio of CBS/S as 1.6/2.2 phr was regarded as the acceptable combination in designing green cushion gum composite formula. Higher CB N330 loading in hybrid filler composition and conventional curing system attributed to the relatively high crosslink density indicated by MH-ML value. Consequently, green cushion gum composite was obtained using the RF1 formula that has a better optimum curing time accompanied by good tensile property and adhesion strength. The composite was also comparable to conventional commercial cushion gum.